Mining Big Data in statistical systems of the monetary financial institutions (MFIs) - Ashofteh, Afshin (2018)
Ashofteh, A. (2018). Mining Big Data in statistical systems of the monetary financial institutions (MFIs). Congress UPV. 2nd International Conference on Advanced Research Methods and Analytics (CARMA 2018) (Abstratcts). Editorial Universitat Politècnica de València . ISBN: 978-84-9048-689-4 (print version). DOI: http://dx.doi.org/10.4995/CARMA2018.2018.8742